The Macro-Stability of Swiss WIR-Bank Credits: Balance, Velocity, and Leverage. Issue 4 (December 2016) - Stodder, James; Lietaer, Bernard
Since 1934, the SwissWirtschaftsring/Cercle Économique (Economic Circle), now the WIR-Bank, has issued its own currency, not backed by Swiss Francs. Turnover in WIR is countercyclical: firms use it more in a recession. A money-in-the-production-function model implies that this spending arises through larger WIRBalances for larger firms, but greater WIRVelocity for smaller ones. Panel data by industrial sector confirm this pattern, similar to commercial trade credits, a major source of non-bank credit. The countercyclical multiplier on WIR expenditures is highly leveraged, and its impact on the Swiss Economy greater than its turnover would suggest.